Real-Life Nature-Based Experiences as Keys to the Writing Workshop - Margot Kinberg (Networks: An Online Journal for Teacher Research, 2020)
For many years, research has supported the value of using real-life experiences as teaching opportunities (e.g. Noobanjong & Louhapensang, 2017; Powell, 2015). This is just as true of teaching writing as of anything else. In fact, when learners use writing (such as journaling) to share their experiences, they benefit in several ways, including their communication skills (e.g. Khanmohammad & Eilaghi, 2017). Writing workshops have been shown to be effective approaches to coaching writing at several different levels (Williams, 2014). Such workshops provide the opportunity to reflect on drafts, collaborate with peers and work through the writing process. They are, therefore, a highly effective context in which to integrate writing about real-life experiences. This, in turn, allows students to develop their writing and their content knowledge. In order to investigate the integration of real-life writing practices into the writing workshop, we focused on a natural setting, and created a writer’s workshop, Writing in Nature, for students in the upper-elementary/middle grades (ages 10-12). During the two-session workshop, we provided students with a nature context. Then, we led them in a writing workshop. Results showed high student engagement and interest, both in the topic and in writing. Our findings suggest that using a natural setting for writing workshops is an effective real-life context for increasing engaged time, teaching content, and developing writing skills. Key Words: Writing Workshop; Teaching of Writing; Experiential Learning; Natural Setting
Keywords: Writing Workshop; Teaching of Writing; Experiential Learning; Natural Setting